Profile of Reticulocyte Hemoglobin Equivalent (Ret-He) and Red Cell Distribution Width Coefficient of Variation (RDW-CV) in Patients with Hemoglobin Levels Below 8 - Nafilah, Putri Anjani; Mastiadji, Bekti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Anemia is defined as a reduction in the concentration of hemoglobin within red blood cells (erythrocytes). It occurs when hemoglobin levels fall below 12 g/dL. Examination of Reticulocyte Hemoglobin Equivalent (Ret-He) and Red Cell Distribution Width Coefficient of Variation (RDW-CV) in patients with hemoglobin levels below 8 can assist in diagnosing and monitoring various medical conditions such as anemia and erythrocyte disorders. This study aimed to describe the Ret-He and RDW-CV profiles in patients with hemoglobin levels below 8 g/dL. Method: This research employed a descriptive design with purposive sampling, involving 30 samples. Result: The study revealed that among 30 samples, 1 patient (3%) had high Ret-He and high RDW-CV, 4 patients (13%) had normal Ret-He and high RDW-CV, 3 patients (10%) had low Ret-He and normal RDW-CV, 20 patients (67%) had low Ret-He and high RDW-CV, and 2 patients (7%) had normal Ret-He and normal RDW-CV. Conclusion: The highest proportion, 20 patients (67%), showed low Ret-He and high RDW-CV. This finding indicates that the bone marrow response was less active, resulting in immature red blood cells lacking sufficient iron content, thereby limiting normal hemoglobin synthesis in reticulocytes. Furthermore, the presence of increased RDW-CV reflects anisocytosis, or variation in red blood cell size.